2023
DOI: 10.1097/bor.0000000000000930
|View full text |Cite
|
Sign up to set email alerts
|

Acute and postacute COVID-19 outcomes for patients with rheumatoid arthritis: lessons learned and emerging directions 3 years into the pandemic

Abstract: Purpose of reviewTo summarize the findings of studies investigating patients with rheumatoid arthritis (RA) and risk of acute and postacute COVID-19 outcomes 3 years into the pandemic. Recent findingsMost studies early in the pandemic included all patients with systemic autoimmune rheumatic diseases (SARDs), not only those with RA, due to limited sample size. Many of these studies found that patients with SARDs were at higher risk of COVID-19 infection and severe outcomes, including hospitalization, hyperinfla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 73 publications
(104 reference statements)
0
3
0
Order By: Relevance
“…Different from this, an increase of ischemic events in giant cell arteritis (GCA) has been reported during pandemic in Italy, which was largely due to failure to receive timely medical care ( 23 ). Some other studies have also reported risks of developing serious outcomes in people with rheumatic diseases after COVID-19 infection ( 24 26 ). Moreover, the COVID-19 Global Rheumatology Alliance Vaccine Survey found that about 25% of patients with ARDs had PASC ( 27 ), which was similar to our study (26.38%).…”
Section: Discussionmentioning
confidence: 97%
“…Different from this, an increase of ischemic events in giant cell arteritis (GCA) has been reported during pandemic in Italy, which was largely due to failure to receive timely medical care ( 23 ). Some other studies have also reported risks of developing serious outcomes in people with rheumatic diseases after COVID-19 infection ( 24 26 ). Moreover, the COVID-19 Global Rheumatology Alliance Vaccine Survey found that about 25% of patients with ARDs had PASC ( 27 ), which was similar to our study (26.38%).…”
Section: Discussionmentioning
confidence: 97%
“…Others have found that lower serum butyrylcholinesterase activity is associated with severe COVID-19 [17]. Patients with rheumatoid arthritis have also been shown to have an increased risk of suffering from severe COVID-19, even though this association may be affected by factors such as immunosuppressive medications and concomitant interstitial lung disease [18]. Collectively, these genetic associations may contribute to the understanding of ADAM17 and its potential implications in relation to severe COVID-19.…”
Section: Discussionmentioning
confidence: 98%
“…Coronaviruses use membrane ACE2 receptors to enter human cells. At the same time, ACE2 is also highly expressed in lung cells of patients with RA-related interstitial lung disease (ILD), and patients with RA and ILD are more susceptible to high inflammation and acute lung injury than the general population 17 , 18 . In addition, RA-ILD and COVID-19-infected lung lesions have remarkable similarities in epidemiological, clinical, and immunological characteristics.…”
Section: Discussionmentioning
confidence: 99%